(Re-)construing Space as Capital: Contributions from a Study with Local Entrepreneurs - Anderson de Souza Sant'Anna; Daniela Martins Diniz (BBR: Brazilian Business Review)
Taking as reference the approaches adopted by Bourdieu (2010) and Jacobs (2011), the focus of this article is to present the findings of a research effort designed to investigate the relationships between the constructs Space and Social Dynamics. In this sense, it seeks to investigate in which manner did the relationships among different social agents – emphasizing the roles played by local entrepreneurs – which, upon mobilizing different capitals – economic, social, cultural and symbolic (BOURDIEU, 2010) – shape and are shaped by specific spatial configurations, creators of socio-spatial dynamics that are diversity-enablers to a greater or lesser extent (JACOBS, 2011). For this purpose, an investigation inspired on the Grounded Theory was undertaken, involving documentary analysis, direct observation and 41 semi-structured interviews with entrepreneurs, dwellers, passers-by and opinion leaders inserted into the dynamics of an important peripheral street in the city of Sete Lagoas/MG. Notable findings include the relevance of studies that draw more systematic considerations, extrapolating economic, social, cultural and symbolic capitals (BOURDIEU, 2010), allocating a greater importance to “spatial capital”, usually relegated to a secondary plane not only in Bourdieu’s “Theory of Practical Action” as well as in classical studies into Economics and Geography (SANTOS, 2012). Another of this study’s significant findings is that the subjects personified in the different types of entrepreneurs identified – Traditional, Modern and Bricoleurs – do not emerge nor act in a socio-spatial void, nor are independent from each other. Quite the opposite, they are a part of a community social ecology (HANNAN; FREEMAN, 1984), rife with dispute, collaboration and intentional and unconscious synergies, in which space, in addition to technological-economical forces, plays a relevant role.